Contradições da democracia: a dualidade entre discurso de ódio e liberdade de expressão nas mídias sociais - Couto, Mara Rúbia Duarte (2021)
Considering the increase of intolerance to differences on social media sites, there was a need to study the phenomenon of hate speech, delimiting the extent of the right to freedom of expression without it becoming an aggression to human dignity. Therefore, the question-problem that drives this research is: how to identify the tolerable limits between freedom of expression and hate speech? Thus, this research aims to analyze the discursive composition of content involving hate speech published on social media and create a parameter that can serve as a basis for distinguishing the right to freely express oneself from hate speech. For this, an empirical qualitative research was carried out, starting with an exploratory research and followed by a literature review, then was determined as a methodological approach for data analysis the perspective of Discourse Analysis. Data were collected manually from pages and public groups on the Facebook platform, in the period between the second half of 2020 and early 2021. The results showed that hate speech operates as a threat to democracy, as it tries to silence the victim, hurting the communicational citizenship of democracy and putting it in contradiction. It was also ratified that no right is absolute and that limiting the right to express an opinion is a way of ensuring that everyone enjoys it. It was reiterated the hypothesis that the limit between one element and another of the problem-question is that an alleged opinion is characterized as hate speech when shared and affects a minority group with its discriminatory characteristics. We propose society's media and information literacy as a possible long-term solution and counter-narratives, as well as more severe and recurrent punishments, as short-term responses.